45. EVALUATION OF THE EFFECTIVENESS AFTER IMPLEMENTING THE AIDET COMMUNICATION MODEL FOR NURSES AT NINH BINH PROVINCIAL OBSTETRICS AND PEDIATRICS HOSPITAL, 2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: (1) To assess the rate at which nurses apply the AIDET model in patient communication. (2) To evaluate the effectiveness of the AIDET model at Ninh Binh Obstetrics and Pediatrics Hospital. Subjects and Methods: A cross-sectional descriptive study was conducted on 140 patients/caregivers (P/CG) and 69 nurses and midwives (N/M).Results: The average AIDET implementation rate among N/M was as follows: A (Acknowledge): 97.06% (SD = 3); I (Introduction): 84.03% (SD = 8); D (Duration): 91.27% (SD = 3); E (Explanation): 96.73% (SD = 3); T (Thanks): 81.8% (SD = 9). The effectiveness of AIDET implementation, as assessed by P/CG before and after application, was: A: 60.7% before, 97.8% after; I: 33.6% before, 83.5% after; D: 53.6% before, 91.4% after; E: 64.3% before, 93.6% after; T: 30% before, 90.7% after. Patient satisfaction levels with N/M communication improved significantly: Very dissatisfied: 1.4% before, 0% after; Dissatisfied: 2.1% before, 0% after; Neutral: 30% before, 5.0% after; Satisfied: 42.9% before, 49.3%fter; Very satisfied: 23.5% before, 45.1% after.Conclusion: The implementation of the AIDET communication model by nurses at Ninh Binh Obstetrics and Pediatrics Hospital was highly effective. The differences before and after the study were statistically significant, particularly in greeting, providing information, and explaining to patients/family members, which showed remarkable improvement over time. The effectiveness of applying the AIDET communication model was highly appreciated by PT/FM, as reflected in the increased satisfaction rates after its implementation.
Keywords: AIDET; Ninh Binh; P/CG; N/M